2022
DOI: 10.1093/icvts/ivac132
|View full text |Cite
|
Sign up to set email alerts
|

How can the rate of nontherapeutic thymectomy be reduced?

Abstract: Objectives To determine the prevalence of nontherapeutic thymectomy and define a clinical standard to reduce it. Methods From 2016 to 2020, consecutive patients who underwent thymectomy were retrospective reviewed. Univariable and multivariable analyses were used to identify the correlation factors of nontherapeutic thymectomy. A receiver operating characteristic (ROC) curve was analyzed to assess the cutoff threshold of fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Wang et al. ( 8 ) retrospectively reviewed 1,039 consecutive patients who underwent thymectomy. Multivariable analysis indicated that patients younger than 44 years old with a precontrast/postcontrast CT value (DCT value) of less than 6 HU had a 95% probability of nontherapeutic thymectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al. ( 8 ) retrospectively reviewed 1,039 consecutive patients who underwent thymectomy. Multivariable analysis indicated that patients younger than 44 years old with a precontrast/postcontrast CT value (DCT value) of less than 6 HU had a 95% probability of nontherapeutic thymectomy.…”
Section: Discussionmentioning
confidence: 99%